2013
DOI: 10.1371/journal.pone.0069367
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants in Hormone-Related Genes and Risk of Breast Cancer

Abstract: Sex hormones play a key role in the development of breast cancer. Certain polymorphic variants (SNPs and repeat polymorphisms) in hormone-related genes are associated with sex hormone levels. However, the relationship observed between these genetic variants and breast cancer risk has been inconsistent. We conducted a case-control study nested within two prospective cohorts to assess the relationship between specific genetic variants in hormone-related genes and breast cancer risk. In total, 1164 cases and 2111… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…In a large study of Chinese women, Zhang et al (2011) reported that SHBG rs6259 was significantly associated with BC risk in stage I and II combined analyses, in which Global haplotype association P value: 0.0025. the minor allele (A) produced a reduced risk of disease. However, Clendenen et al (2013) and Diergaarde et al (2008) found no association between rs6259 and BC risk, which is in agreement with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…In a large study of Chinese women, Zhang et al (2011) reported that SHBG rs6259 was significantly associated with BC risk in stage I and II combined analyses, in which Global haplotype association P value: 0.0025. the minor allele (A) produced a reduced risk of disease. However, Clendenen et al (2013) and Diergaarde et al (2008) found no association between rs6259 and BC risk, which is in agreement with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Four studies have shown an elevated risk for breast cancer with the UGT1A1*28 allele in African American (Guillemette et al 2000), Chinese (Adegoke et al 2004), Russian (Shatalova et al 2006) and German (Marie-Genica 2010) women. However, four other studies have shown no association of UGT1A1*28 with breast cancer risk in Taiwanese (Cheng et al 2005), Greek (Tsezou et al 2007), or European American (Guillemette et al 2001) women, or in a mixed population of American and Swedish women (Clendenen et al 2013). Furthermore, one study showed a decreased risk of UGT1A1*28 for breast cancer in Nigerian women (Huo et al 2008).…”
Section: Discussionmentioning
confidence: 97%
“…In another study, 95 postmenopausal women with stage II–III ER-positive breast cancer were treated with neoadjuvant letrozole, and only rs4646 was associated with a poor response ( P = 0.03) [17]; progression-free survival was reduced in patients carrying (CA/AA) variants compared with those with the reference CC variant [17]. In other recent studies, rs4646 was shown to have no association with breast cancer outcome or risk [18, 20, 22]. In addition, rs700519 SNP variants in exon 7, when compared with the wild-type genotype, have been associated with an increased risk of breast cancer among Hawaiian, Japanese [23], and Korean women [24].…”
Section: Discussionmentioning
confidence: 99%